2011
DOI: 10.1248/jhs.57.521
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Research for the Anti-obesity Effect of Puerariae Flos Extract in Humans

Abstract: This research is preliminary study to examine whether puerariae flos extract (PFE) makes any action to body fat of man or not. We conducted the double-blind placebo controlled study on eighty mildly obese subjects for 8 weeks. The subjects were randomly divided into 4 groups: I, II, III, and IV. Subjects in groups I, II, and III consumed test food containing 100, 200, and 300 mg PFE, respectively, while those in group IV were given placebo food for 8 weeks. All subjects were instructed to restrict their total-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Thus, PFE might be expected to prevent NASH by suppressing hepatic lipid accumulation. In fact, GOT, GPT, and gamma-GTP expressions were significantly reduced by PFE ingestion in our preliminary clinical study [5]. This result supports the possibility that PFE supplementation provides the dual effects of preventing both obesity and hepatic disorders.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, PFE might be expected to prevent NASH by suppressing hepatic lipid accumulation. In fact, GOT, GPT, and gamma-GTP expressions were significantly reduced by PFE ingestion in our preliminary clinical study [5]. This result supports the possibility that PFE supplementation provides the dual effects of preventing both obesity and hepatic disorders.…”
Section: Discussionsupporting
confidence: 77%
“…6) Many pharmacological studies reported the extensive biological activities of the flower, including hepatoprotective, antioxidant, hypoglycemic, and hypolipidemic activities. 5,7,8) The phytoestrogenic isoflavonoids and saponins are the major components in the flowers as well as roots, [9][10][11] and should be responsible for these aforementioned activities. [12][13][14] The current study is focusing on both Pueraria flowers because the phytopharmaceuticals containing the Pueraria flower, such as the Pueraria flower tea and drink, 15) have become popular for the treatment of alcohol intoxication and liver injury in China and Japan.…”
mentioning
confidence: 99%
“…In China, tea made from dried Kudzu flowers is widely consumed [1], and PFE is consumed as a nutritional supplement for the treatment of hangovers and obesity in Japan. We previously reported that PFE exerts anti-obesity effects in humans and mice fed high-fat diets [2][3][4]. In addition, we also reported that the isoflavone-rich fraction of dietary PFE exhibits anti-obesity effect in mice fed high-fat diets [5].…”
Section: Introductionmentioning
confidence: 83%